RECONFIGURING "NATIONAL ALLEGORY" IN A CRITIQUE OF THE PHILIPPINE NEOCOLONIAL EXPERIENCE. - San Juan Jr., E. (Kritika Kultura, 2026)
With appropriate adjustments, Jameson’s theory of national allegory can serve as a serviceable frame to interpret Filipino texts. Allegory as figuration or image-thinking aims to resolve conceptual blockage or theoretical dead-ends. Analyzing an exemplary story by Lualhati Bautista, this essay seeks to demonstrate how the author’s mode of representation captures the effect of combining feudal-archaic and capitalist modes of production in the lives of typical characters. Private thoughts and feelings conflict with public norms in the predicament of two uprooted protagonists caught in the crisis of a disaggregated polity. The Philippine social formation as a dependent entity exemplifies the mix of archaic-feudal and reified life-ways brought about by U.S. colonization. Bourgeois norms are superimposed on family-kinship networks that produce schizoid actions crisscrossing borders of normality, revealing the limits of the neocolonial order. Everyday life, quotidian experience in flux, thus becomes the arena for the production of inconsistent practices and ambivalent responses. They function as symptoms reflecting the uneasy amalgam of residual/hegemonic structures and emergent ones. Given this interweaving, literal and allegorical levels of meaning serve to prefigure the moral and anagogical domains where we observe the dissolution of the rational subject and the reaffirmation of the old system. An imaginary resolution of contradictions between individual revolt and patriarchal law emerges in an ambiguous return to the initial situation of alienation, subordination, and fantasy. What figuration uncovers is the real source of the crisis: the contradiction between a new mode of material reproduction and the obsolete, futile social relations. The problematic ideal of a neocolonial community is revealed as a fictional illusion based on real-life violence and suffering, which the concept of national allegory is intended to register as a unique kind of "third-world" discourse.